Vortex state in ferromagnetic nanoparticles - COEY, JOHN (My University, 2014)
The evolution of the magnetic state of a soft ferromagnetic nanoparticle with its size is usually thought to be from superparamagnetic single domain to blocked single domain to a blocked multidomain structure. Néel pointed out that a vortex configuration produces practically no stray field at the cost of an increase in the exchange energy, of the order of , where JS 2 is the bond energy, R is the particle radius, and c is of the order of the exchange length. A vortex structure is energetically cheaper than single domain when the radius is greater than a certain value. The correct sequence should include a vortex configuration between the single domain and the multidomain states. The critical size is calculated for spherical particles of four important materials (nickel, magnetite, permalloy, and iron) both numerically and analytically. A vortex state is favored in materials with high magnetisation.
PUBLISHED
Keywords: soft ferromagnetic nanoparticle; soft ferromagnetic nanoparticle